Determination of Physical and Social Vulnerability Zones In Cisarua District, West Bandung Regency, Using Remote Sensing and Geographical Information Systems - Pamungkas, Totok Doyo; Somantri, Lili; Aliyan, Silmi Afina; Firdaus, Rival Akbar (Jurnal Pendidikan Geografi Gea, 2024)
Cisarua is an area in West Bandung that is categorized as prone to earthquakes due to its position close to the Lembang fault. Research in determining physical and social vulnerability zones is needed to reduce the impact of earthquake disasters and determine the relationship between social and physical vulnerability. The research approach uses quantitative analysis with scoring, weighting, and overlay using remote sensing spatial analysis and geographic information systems. Data collection techniques for physical vulnerability variables are secondary data indicators of building density, length of the road network, and the number of permanent buildings, while social vulnerability variables are secondary data indicators of population density, population under five, elderly, women, and persons with disabilities. The results of the study obtained a mapping of the level of physical vulnerability in Cisarua District with a very high score, namely Jambudipa Village, while the lowest scores were in the areas of Pasirhalang Village, Padaasih Village, Tugumukti Village, Sadangmekar Village, and Cipada Village. For mapping the level of social vulnerability in Cisarua District, a very high score was found in the Jambudipa Village area and very low in Tugumukti Village. The two levels of vulnerability produce a relationship pattern of linearity comparison of scores between physical and social. It is related to population density indicators that affect building density